Hubungan Antara Self Monitoring Dengan Perilaku Konsumtif Pada Mahasiswa Fakultas Psikologi Universitas Muhammadiyah Surakarta - Widodo, Bintang Prayoga, Drs. Mohammad Amir, M.Si , Psi (2016)
Consumtive behavior at collegian caused of collegian characteristic as teenager and youth who can persuaded from anythings and their social comunity. Self Monitoring is an effort that doing by someone to look up theirself in front of another one with clue that comes from inside and outside theirself. Sometimes people buy a product is not depend on their needs but they want to look great . thats why consumtive behavior may comes. One aspect that can made consumtive behavior is self monitoring. Purpose of this reseach are: 1) To know the correlation between Self Monitoring and Consumtive Behaviour 2) To know effective contribution of Self Monitoring on the Consumtive Behaviour 3) To know the level of Self Monitoring of collegian at faculty of psychology 4) To know the level of Consumtive Behaviour of collegian at faculty of psychology Subjects in this research are Collegian from Faculty of Psychology Muhammadiyah University Surakarta who study at semester 1-8 as much as 100 people, the technique of sampling which was used was purpossive samplinh. The method of data collection used of the scale of Self Monitoring and the scale of Consumtive Behaviour. The technique of data analysis used correlation product moment Based on results of Product Moment, it was obtained the score of corefficient of rxy as much as 0,036; (p) = 0,360 (p>0,05) which mean that there was no correlatin between Self Monitoring and Consumtive Behaviour. Subject in this research had a level of Self Monitoring in the high category with an empirical mean as much = 53,45 and hypothetical as much as = 45 Subject also had Medium level of Consumtive Behavior with an empirical mean as much = 46,7 and hypothetical as much as = 47,5